Accurate and versatile simulation of transient voltage profile of lithium-ion secondary battery employing internal equivalent electric circuit. (1st April 2015) - Tanaka, T.; Ito, S.; Muramatsu, M.; Yamada, T.; Kamiko, H.; Kakimoto, N.; Inui, Y.
Highlights: Simulation method for voltage profile of lithium-ion secondary battery is proposed. Three test batteries with different output power density are prepared. Accuracy of the proposed method is confirmed for all test cases. The proposed method is very helpful to establish various battery control systems. Abstract: This paper presents a new numerical simulation method to calculate transient voltage profiles of lithium-ion secondary batteries. The method employs circuit analysis of an internal equivalent electric circuit composed of an electromotive force, an LR parallel circuit, and eight CR parallel circuits. To demonstrate the accuracy and versatility of this approach, the authors measured the transient voltage responses of three types of test batteries with different output power densities, and compared these experimental data with simulation results. Battery performance was tested using different charge/discharge current patterns and a range of values for state of charge (SOC) and operating temperature. The accuracy of the proposed simulation method was confirmed for all test cases using the three different batteries and charge/discharge current patterns, demonstrating that the method is versatile and applicable to various lithium-ion secondary batteries regardless of type. Since the employed internal equivalent electric circuit is composed of only DC voltage source and linear R, L and C elements, all of general purpose software for electric circuit simulations can easily deal with the circuit. This advantage and the obtained results indicate that the proposed simulation method is a useful technique and offers a powerful tool to develop sophisticated battery control systems for various applications.